Problematika Guru Pendikan Agama Islam Dalam Pembelajaran Fikh Di Sekolah Umum - Firman Mansir; Halim Purnomo (Jayapangus Press, 2020)
This study explores the numerous problems that come up from teachers of Islamic Religious Education in public schools. Learning in fiqh is learning based on an interpretation of a topic that comes from the al-Qur'an and al-Hadith. As it is understood that each individual or group 's understanding has to be different, it all depends on the point of view or how to interpret the various problems that occur in learning fiqh. Particularly in public school learning which has different nuances from madrasah and Islamic boarding schools. Every educational institution, under the auspices of Islamic mass organisations and public schools, has different problems. Thus, this study explores what are the issues with public schools studying jurisprudence. The aim of this study was to recognize the different problems faced by educational institutions, in this case fiqh learning in public schools. The approach used in this analysis is a qualitative method by evaluating the fiqh learning difficulties that arise in public schools, both through the perspective of the teachers themselves and the students.